Impact of high performance work practices on employees' performance in Pakistan: Mediating role of employee engagement - Adeel Akhtar; Muhammad Kashif Nawaz; Zeeshan Mahmood; Muhammad Sadiq Shahid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The financial sector of Pakistan has been witnessing high growth since the last two decades. Due to increase of branch network, competition among banks has increased. In this intense competition, employees play pivotal role in the competitiveness of financial sector. To line with this, this study aims to find the impact of high performance work practices on employees' performance through mediating role of employee engagement in banking sector of Pakistan. For this purpose, data were collected from employees working in the banking sector of district Multan, Pakistan. Questionnaire was used as a tool for data collection from a sample of two hundred employees. Statistical Package for Social Sciences version 17 was used for data analysis. Factor analysis and Cronbach's alpha was used to test the validity and reliability of the measured constructs. Similarly, correlation and regression analysis indicated that all the study variables were positively related to each other. More specifically, high performance work practices had positive and significant impact on the employee engagement and employee performance. Furthermore, it was also confirmed that employee engagement mediated the relationship between high performance work practices and employee performance.
Keywords: 330; High performance work practices; Employee Engagement; Employee Performance; Financial Sector; Pakistan